SENSUALITAS DALAM KONTEN “YOUTUBE’S GOT TALENT” PADA CHANNEL SKINNYINDONESIAN24 - Syifa Syarifah Alamiyah (LPPM Universitas Negeri Surabaya, 2024)
Youtube is a widely accessed new media. During its development, Youtube has enabled its viewers to become producers and consumers. This has resulted in many new profit-oriented content creators, by creating content with sensual elements. This has reaping criticism from previous content creators on Youtube, one of them is SkinnyIndonesian24. This study aims to see how SkinnyIndonesian24 packs a criticism of sensuality through the content